Analysis of the Expected Cross Aisle Travel Distance: For Multi-Picks and Multi-Aisles Conditions - Chandra, Agung (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2017)
Purpose: The purpose of this research is to find the impacts of multi picks multi aisle on expected cross aisle travel distance for one picker at layout with parallel picking aisles and orthogonal cross aisles at each end of the picking aisles. Design / methodology / approach: Using the theory of expected mean value to calculate expected number of cross aisle width in multi-picks and multi-aisles conditions Findings: the results show that the expected cross aisle travel distance is affected by the expected number of aisle width and number of picks Research limitations / implications: Further research is needed to explore the other type of layout in order to get the shortest distance. Secondly, the further research needs to analyze the picking activity is done by more than one pickerPractical implications: This is the early beginning study to get the shortest cross aisle travel distance that may be used for professional engineer to design and to choose the best layout for the condition – multi-picks and multi-aisles conditions Originality / value: This study shows the impact of number of aisle width and number of picks on the cross aisle travel distance by using the theory of expected mean value.